INTEGRASI SMART FINANCIAL HABITS DAN PEMBUKUAN SEDERHANA PADA PELAKU UMKM - Rahmawati, Asmannisa; Mahardian Mustiko Nugroho; Siti Marwati; Nabila Qotrunnada; Marcos Lafu Caunan; Hari Tripanto Silitonga; Dian Nala Damayanti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to examine the integration of smart financial habits and simple bookkeeping to enhance the financial management capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Tegal City. A descriptive approach was employed through socialization activities and direct mentoring, complemented by an evaluation stage to systematically assess participants’ levels of understanding. The results indicate that the integration of smart financial behavior and simple bookkeeping increases MSME owners’ awareness of the importance of more planned and systematic financial management. Participants demonstrated improved understanding in separating personal and business finances, along with enhanced ability to apply accurate and consistent business bookkeeping practices. This program shows that the implementation of smart financial habits not only plays a crucial role in strengthening financial management but also supports business sustainability by improving the credibility of financial records, thereby facilitating MSMEs’ access to formal financing sources.